STUDI KEMAMPUAN SISWA TAHUN KEDUA SISWA SMP TUAH NEGERI PEKANBARU DALAM KEMAMPUAN LISTENING PADA TEKS NARATIF - Maryah Nur Ulfa; Jismulatif Jismulatif; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research is aimed at finding out the ability of the second year students of SMP Tuah Negeri Pekanbaru in listening comprehension on narrative texts. The subjects of this research were class VIIIB which consist of 35 students. The data collected on April 2017, used multiple choice question which consist of 20 questions from 4 components; finding main idea, detail information about the story, inference and restatement. Based on the data analysis, it was found that the ability of second year students in listening comprehension on narrative texts was classified into excellent level with mean score of 80.99. Next, the students’ mean score in finding the main idea was in excellent level with the mean score of 80.57. Finding detail information about the story was categorized into excellent level with the mean score of 81.71. Getting inference can be grouped into excellent level with mean score of 81.14. Finding restatement can be considered into excellent level with mean score of 80.57. As a conclusion, the highest score obtained by the students was in finding detail information about the story with the mean score of 81.7 (excellent). It means the use of listening material in teaching narrative text is suitable to the research subjects. It would be better to recommend the other researcher to conduct relevant study on the narrative text.Keyword: Listening comprehension, Narrative text.